Karakteristik Kimia dan Sensori Hard Candy Black Garlic dengan Penambahan Madu dan Lemon: The Chemical and Sensory Characteristics of Black Garlic Hard Candy With The Addition of Honey and Lemon - Zakiyyah, Syahla; Puspasari, Erna; Nurlaela, Raden Siti (Jurnal Ilmiah Pangan Halal, 2025)
Black garlic has a lighter aroma than garlic, sweet-sour taste, chewy texture, and contains antioxidants twice as high as garlic, making it a potential alternative in product development. This study aims to develop the utilization of black garlic as an ingredient in the production of hard candy and to examine its chemical and organoleptic characteristics. This study used a one-factor Completely Randomized Design (RAL) with three treatment levels of black garlic extract concentration (A1 = 5 mL, A2 = 10 mL, and A3 = 15 mL) repeated twice. The analysis included chemical tests (water content, ash content, reducing sugar, and saccharose) and organoleptic tests (sensory and hedonic quality) on color, texture, aroma, taste, aftertaste, and overall black garlic hard candy. Antioxidant activity test was conducted on selected products. The results showed that the selected black garlic hard candy was obtained by adding 10 mL of black garlic extract, with chemical characteristics in the form of 0.91% moisture content, 0.008% ash content, 11.05% reducing sugar, and 79.54% sucrose. The antioxidant activity was classified as weak with an IC₅₀ value of 157,713.52 mg/L and a TEAC value of 10.85 mg/100g. This study shows that the use of black garlic in hard candy products with added honey and lemon has the potential to become an innovative and consumer-friendly alternative for halal food diversification.